Optimalisasi Tiktok Sebagai Media Pembelajaran Untuk Mendukung Dampak Psikologis dan Keuntungan Finansial - Nazmah, Nazmah; Akbar, Aswin; Purnama Sari, Dian (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
This community service aims to optimize the use of TikTok as an interactive and economically potential learning medium for students and teachers at SMA Harapan 3 Medan. The primary issue identified was the participants' lack of understanding regarding the utilization of social media for educational purposes and monetization. The solution was provided through a workshop based on seven literacies: digital, technological, media, financial, informational, social, and cultural. The implementation methods included theoretical sessions, practical applications, evaluations through pre-tests and post-tests, and follow-up surveys. Results indicated an improvement in participants' understanding, with 85% of students able to create educational content after the training, and 70% of them understanding monetization strategies. The workshop also motivated 60% of teachers to consider social media as a teaching aid. The impact of this activity is expected to continue in adaptive learning and the creative economy in the digital er.